The Formation of the Asylum in Upper Canada - Edginton, Barry (My University, 1981)
The purpose of this dissertation is to develop an explanation for the formation of a lunatic asylum in early nineteenth century Upper Canada. In order to understand the separate institutionalization of the mad in lunatic asylums, I examine the asylum within the context of the transformations in social life in the late eighteenth and early nineteenth centuries.
The dissertation addresses the question: Why in the period 1841-53 did the Upper Canadian State provide for the separate institutionalization of the mad in asylums? This question has led to the investigation of events and social processes prior to the establishment of the Toronto Lunatic Asylum which determined its formation. In order to understand the event of asylum formation. I have introduced a holistic explanation based in the general principles of Marxist political economy.
Embedded within an explanation of asylum formation in Upper Canada is not only the social structure of Upper Canadian Society but also the history of the confinement of the mad prior to asylums. The latter covers the confinement of the mad within the institutions of public welfare and their association with poverty. Since Upper Canada was a colony of Great Britain, its organization was closely tied to Britain. Their histories are intertwined and their methods of incarceration similar.
This dissertation illustrates the point at which the inasne were pushed out of the institutions of public welfare and into the hands of the medical profession. Asylum formation is an event that marks the end of one era of treatment or the mad and the birth of another. It is an event which begins the process of separating the mad from the poor and associating the mad with the sick, a process which, in its institutional form, took over a century to complete.
Keywords: Sociology; Sociology